Prognostic Role of Systemic Inflammatory Indexes in Germ Cell Tumors Treated With High-Dose Chemotherapy - Cursano, Maria Concetta; Kopf, Barbara; Scarpi, Emanuela; Menna, Cecilia; Casadei, Chiara; Schepisi, Giuseppe; Lolli, Cristian; Altavilla, Amelia; Gallà, Valentina; Santini, Daniele; Tonini, Giuseppe; Chovanec, Michal; et al. (Frontiers in Oncology, 2020)
High dose chemotherapy (HDCT) has curative potential in relapsed/refractory germ cell tumors (GCT). Since the complexity of this population and the toxicity of HDCT, we evaluated the association between blood-based systemic inflammatory indexes and outcome of GCT patients undergoing salvage treatment with HDCT in order to define additional prognostic factors able to orient clinical decision. Baseline characteristics, neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR) and the systemic immune-inflammation index (SII) of 62 patients undergoing HDCT for GCT were retrospectively collected. The aim is to evaluate the correlation between each inflammatory marker (NLR, PLR and SII) and response to HDCT, overall survival (OS) and progression free survival (PFS). Using the receiver operating curve (ROC) to identify the best cut-off values, it was found that patients with GCT with NLR ≥3.3 and SII ≥844000 had shorter PFS and inferior OS. In the multivariable analysis including inflammatory markers, IPFSG risk group, age and previous line of treatment, NLR ≥3.3 and SII ≥844000 were identified to be independently associated with shorter PFS and OS. Moreover, NLR, PLR and SII significantly correlate with overall response to HDCT. Associating IPFSG prognostic score to inflammatory markers at baseline of HDCT may improve prognostic information and could help physicians to make more personalized treatment decisions.